Non-coding RNA regulation in reproduction: Their potential use as biomarkers - Vanesa Robles; David G. Valcarce; Marta F. Riesco (Non-coding RNA Research, 2019)
Non-coding RNAs (ncRNAs) are crucial regulatory elements in most biological processes and reproduction is also controlled by them. The different types of ncRNAs, as well as the high complexity of these regulatory pathways, present a complex scenario; however, recent studies have shed some light on these questions, discovering the regulatory function of specific ncRNAs on concrete reproductive biology processes. This mini review will focus on the role of ncRNAs in spermatogenesis and oogenesis, and their potential use as biomarkers for reproductive diseases or for reproduction success. Keywords: Non-coding RNAs, Spermatogenesis, Oogenesis, Reproductive transgenerational effects, Biomarkers